Area of Interest Based Assessment of Software Interface Usability for Human-Computer Interaction Using Eye-Tracking - Gordieiev, Oleksandr; Gordieieva, Daria; Kondius, Inna; Lishchyna, Nataliia (My University, 2022)
Non-functional requirements to software quality (SWQ) is described in general by SWQ models characteristics. Last the most famous software quality model ISO/IEC 25010 includes eight characteristics: functional suitability, performance efficiency, compatibility, usability, reliability, security, maintainability and portability. Usability as a SWQ characteristic must include subcharacteristics, inherent to software user interface quality as static object and also as subcharacteristics of process user interaction, i.e. is user-computer interaction in real time. In existing models of quality and quality assessment of usability the peculiarities of humancomputer interaction (HCI) in real time are not taken into account in real time. Software interface usability model (SIUM) for HCI and models for its assessment are suggested. Such models are interconnected through a single nomenclature of subcharacteristics. HCI SIUM consists of two parts and includes a set of metrics, which correspond to the defined under subcharacteristics. Particularity of model is that all primitives for calculation software interface usability metrics for HCI obtained only with use of software and hardware complex of the eye-tracker.
Keywords: human-computer interaction; Interaction quality; metrics usability; software usability